Palbociclib with Letrozole in Postmenopausal Women with ER+/HER2− Advanced Breast Cancer: Hematologic Safety Analysis of the Randomized PALOMA‐2 Trial. (19th June 2019) - Diéras, Véronique; Harbeck, Nadia; Joy, Anil Abraham; Gelmon, Karen; Ettl, Johannes; Verma, Sunil; Lu, Dongrui R.; Gauthier, Eric; Schnell, Patrick; Mori, Ave; Rugo, Hope S.; Finn, Richard S.
Abstract: Background: PALOMA‐2 confirmed that first‐line palbociclib + letrozole improved progression‐free survival (hazard ratio, 0.58; 95% confidence interval, 0.46–0.72) in postmenopausal women with estrogen receptor–positive (ER+)/human epidermal growth factor receptor 2–negative (HER2−) advanced breast cancer (ABC). This analysis evaluated palbociclib‐associated hematologic adverse events (AEs) and provides insight on managing these AEs. Materials and Methods: Postmenopausal women with ER+/HER2− ABC were randomly assigned 2:1 to letrozole (2.5 mg daily continuously) plus oral palbociclib (125 mg daily; 3 weeks on/1 week off) or placebo. Safety assessments were performed at baseline, days 1 and 15 (first two cycles) and day 1 of subsequent cycles, and included white blood cell, platelet, and absolute neutrophil count (ANC). Results: PALOMA‐2 randomized 666 women to palbociclib + letrozole ( n = 444) or placebo + letrozole (n = 222). Neutropenia was the most common AE (95.3%) with palbociclib (grade 3, 55.6%; grade 4, 11.5%) and was managed by dose modifications; progression‐free survival was similar between patients who experienced grade ≥ 3 neutropenia versus those who did not. Median (range) time to onset of neutropenia with palbociclib + letrozole was 15 (12–700) days (grade ≥ 3, 28.0 [12 –54] days); median duration of each neutropenia episode grade ≥ 3 was 7.0 days. Asian ethnicity and low baseline ANC were associated with increased risk of grade 3/4 neutropenia with palbociclib ( p < .001). Conclusion: Palbociclib + letrozole was generally well tolerated. Neutropenia, the most frequently reported AE in women with ER+/HER2− ABC, was mostly transient and manageable by dose modifications in patients who experienced grade ≥ 3 neutropenia, without appearing to compromise efficacy. (Pfizer; NCT01740427) Implications for Practice: Palbociclib demonstrated an acceptable safety profile in PALOMA‐2 in women with estrogen receptor–positive (ER+)/human epidermal growth factor receptor 2–negative (HER2−) advanced breast cancer (ABC) receiving first‐line palbociclib + letrozole. Although hematologic adverse events (AEs) are typically expected with anticancer therapies and are often clinically significant, palbociclib‐related hematologic AEs, particularly neutropenia (most frequent AE), were transient/manageable by dose reduction, interruption, or cycle delay, which is in contrast to the more profound neutropenia associated with chemotherapy. Palbociclib dose adjustments decreased hematologic AE severity without appearing to compromise efficacy, supporting palbociclib + letrozole as a first‐line treatment for ER+/HER2− ABC. Abstract : This article focuses on the safety profile of palbociclib in combination with letrozole, evaluating the clinical patterns of hematologic adverse events in the PALOMA‐2 trial.